Pendampingan Masyarakat Dusun Lidah Wetan dalam Pelestarian Budaya Literasi dengan Pembuatan Perpustakaan Mini dan Taman Baca di Surabaya - Susi Ratnawati (LPPM Universitas Yudharta Pasuruan, 2020)
villages in Surabaya that has a very dense population. In this digital era, children and young people are less aware of the need to read. In the tongue, teenagers are not so concerned with learning. Bhayangkara University in Surabaya held a Community Service program which took place in the Lidah Wetan Hamlet, Lakarsantri District, Surabaya City. With the theme "Preserving Literacy Culture". The program is inseparable from the vision and mission of local village officials. With the mini library created by Community Service Team, Bhayangkara University is expected to increase the enthusiasm and interest in reading in the surrounding community. This mini library provides a variety of books ranging from children's story books, learning books to read, learning books to write, learning books to draw, school materials, to religious nuances books and other books (food recipes, fiction stories, etc.). Some programs are directed at encouraging children's potential in reading culture and fostering youthful enthusiasm in organizing. Nowadays many young people are trying to challenge Karangtaruna. Several agendas are designed to solve these problems.